Exercise and fluid challenge during right heart catheterisation for evaluation of dyspnoea. (June 2020) - Ewert, Ralf; Heine, Alexander; Müller-Heinrich, Annegret; Bollmann, Tom; Obst, Anne; Desole, Susanna; Knaak, Christine; Stubbe, Beate; Opitz, Christian F.; Habedank, Dirk
This prospective study compared exercise test and intravenous fluid challenge in a single right heart catheter procedure to detect latent diastolic heart failure in patients with echocardiographic heart failure with preserved ejection function. We included 49 patients (73% female) with heart failure with preserved ejection function and pulmonary artery wedge pressure ≤15 mmHg. A subgroup of 26 patients had precapillary pulmonary hypertension. Invasive haemodynamic and gas exchange parameters were measured at rest, 45° upright position, during exercise, after complete haemodynamic and respiratory recovery in lying position, and after rapid infusion of 500 mL isotonic solution. Most haemodynamic parameters increased at both exercise and intravenous fluid challenge, with the higher increase at exercise. Pulmonary vascular resistance decreased by –0.21 wood units at exercise and –0.56 wood units at intravenous fluid challenge ( p  = 0.3); 20% (10 of 49) of patients had an increase in pulmonary artery wedge pressure above the upper limit of 20 mmHg at exercise, and 20% above the respective limit of 18 mmHg after intravenous fluid challenge. However, only three patients exceeded the upper limit of pulmonary artery wedge pressure in both tests, i.e. seven patients only at exercise and seven other patients only after intravenous fluid challenge. In the subgroup of pulmonary hypertension patients, only two patients exceeded pulmonary artery wedge pressure limits in both tests, further five patients at exercise and four patients after intravenous fluid challenge. A sequential protocol in the same patient showed a significantly higher increase in haemodynamic parameters at exercise compared to intravenous fluid challenge. Both methods can unmask diastolic dysfunction at right heart catheter procedure, but in different patient groups.